Analisis Usability Aplikasi E-Dosen UIN Raden Fatah Palembang Menggunakan Metode System Usability Scale (SUS) - Reni Septiyanti; Erni Patmawati; Muhamad Son Muarie (Universitas Ma Chung, 2026)
The E-Dosen application is a program developed by the Internal Audit Unit (Satuan Pengawas Internal/SPI) of UIN Raden Fatah Palembang to support lecturers’ performance in providing better services; however, since the application has only recently been implemented, its relatively complex interface has caused confusion for some lecturers, and the large number of features tends to slow down the reporting process. This study aims to evaluate the usability of the E-Dosen application using the System Usability Scale (SUS) method, which includes the variables of effectiveness, efficiency, and satisfaction. Random sampling was employed, involving 240 lecturers as respondents for the SUS assessment and 10 additional lecturers for task scenario testing. The results indicate that the effectiveness level reached 85%, the efficiency value was 0.02877 goals per second showing that tasks could be completed in an average time of 35 seconds per task and user satisfaction, based on a SUS score of 71, fell into the “Good” category, corresponding to Grade C and an acceptable usability scale. Overall, the E-Dosen application is generally usable, although further development is required, particularly in simplifying workflows and the user interface, to enhance speed and user satisfaction.